What is Social Work? Students’ First Approach with the Profession: Experiences from Argentina, Brazil, Paraguay and Uruguay - Rivero-Rodríguez, Silvia Orieta; Del Prado, Leonel; Battilana-Amarilla, Nidia Graciela; Coradini-Guilherme, Rosilaine (Prospectiva. Revista de Trabajo Social e Intervención Social, 2022)
This paper aims to reflect on the first contact that students have with Social Work in their educational process. The introductory course programs of four Latin American countries (Argentina, Brazil, Paraguay and Uruguay) are used as input for analysis. The work shows that despite the differences in each country, the educational training has an emphasis on positions that are framed in the scientific and critical school of thought.